Strukturna pestrost gozdnih sestojev na Pahernikovi gozdni posesti - Pintar, Anže Martin (Acta silvae et ligni, 2018)
On Pahernik's forest estate it is possible to monitor the effects and success of at least half a century of forest management with uneven-aged forests. Based on the data from the control sampling method and the laser scanning of Slovenia, we assessed the structural diversity of forest stands with indicators and indices of stand densities, species and structural diversity of the DBH classes, the stand height classes and their heights. We compared land use in cadastral municipalities where Pahernik property is located (Vuhred, Planina, Orlica and Hudi Kot) in 1825, with land use from 2017. In all of the analyzed cadastral municipalities, the forest area share in land cover grew in the period from the 19th to 21st century. Forest cover increased by 21 % between 1825 and 2014 on Pahernik property as a whole. Differences in stand densities and in stand diversity indices between the stands where forest was not present in the 19th century and the stands on persistently forested lands were not statistically significant. In the prevalent forest site type montane and altimontane Fagus sylvatica forests on silicate bedrock we estimated that growing stock was by 20 % higher than in comparable forests of this site type elsewhere in Slovenia. At higher growing stocks and high values of indices of DBH variability in forests at Pahernik's forest estate, the estimated stand densities SDI were not higher than in forests of comparable forest site types. We estimated differences in height and structure of stand canopy according to the gradients of height classes, which have an impact on forest management within the individual forest type.
Keywords: Franciscejski kataster; Franziscean land cadastre; land use; LiDAR; Pahernikova posest; Pahernik's estate; raba zemljišč; sestojna zgradba; sestojni višinski razredi; stand height classes; stand structure